Effect of Qigong exercise on cognitive function, blood pressure and cardiorespiratory fitness in healthy middle-aged subjects. (August 2017) - Ladawan, Suphannika; Klarod, Kultida; Philippe, Marc; Menz, Verena; Versen, Inga; Gatterer, Hannes; Burtscher, Martin
Highlights: Eight weeks of Qigong training improved attention, brain processing speed, blood pressure and maximal workload in middle-aged subjects. After 12 weeks of detraining, the improvements returned to baseline. Short-term memory was positively correlated with maximal workload and minute ventilation. Abstract: Objective: To investigate effects of Qigong exercise on cognitive function, blood pressure and cardiorespiratory fitness in healthy middle-aged subjects. Methods: Study part 1 examined the effects of Qigong exercise in 12 subjects (5 males, 7 females, aged 52.2 ± 7.1 years) who performed Qigong for 8 weeks (60 min sessions, 3 times/week). Study part 2 evaluated the detraining effects 12 weeks after cessation of Qigong. Cognitive function (Digit Span Forward and Backward Test, Trail Making Tests part A and B), blood pressure, and exercise performance were determined at baseline, immediately after the training programme, and after the detraining period. Results: Qigong exercise showed a significant improvement of Trail Making Tests part A ( p = 0.04), systolic blood pressure ( p = 0.001), diastolic blood pressure ( p = 0.005), mean arterial pressure ( p < 0.001), and maximal workload ( p = 0.032). Twelve weeks after cessation, Trail Making Tests part A, systolic blood pressure, diastolic blood pressure, mean arterial pressure, and maximal workload had returned to baseline ( p = 0.050, 0.007, 0.001, 0.001, and 0.017, compared to after the training, respectively). Conclusion: These results suggest that Qigong exercise effectively improved attention, brain processing speed, blood pressure and maximal workload. However, these improvements disappeared 12 weeks after cessation of Qigong. Consequently, performing Qigong regularly is important to maintain related health effects.